Financial integration in East Africa: evidence from interest rate pass-through analysis - Bholla, Zohaib Salim (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2011)
The successful launch of the European Monetary Union (EMU) raised an already ever growing interest in the economics of monetary integration and the formation of monetary unions around the world. Following the EMU experience, countries have considered forming a monetary union amongst themselves. The East African Community (EAC), comprising the three original member countries Kenya, Tanzania and Uganda and now including Burundi and Rwanda, is an example of such a group of countries that seek to form a monetary union. This study aims to identify the current level of financial integration amongst the East African countries. In order to do so the study examines whether the pass-through of monetary policy in the five countries has become similar over time. This is to provide an indication of the extent to which the nominal convergence criteria amongst the member countries have been met. The results of the study provide an indication of whether the formation of a monetary union in East Africa is possible. The empirical analysis used in this study included stationarity tests, four tests of co integration and an asymmetric error correction model to investigate whether the pass-through of monetary policy transmission in the five countries has become more similar over the ten year sample period from 1999 to 2008. The analysis uses three interest rates and 6-year rolling windows to identify the extent of macroeconomic convergence that prevails within the EAC, and consequently whether the formation of a monetary union is possible. The results suggest that the magnitude of the convergence amongst the countries remain low and there are significant rigidities in the deposit and lending rates over time, however the passthrough has improved with respect to the lending rate but not the deposit rate. The overall conclusion of the study suggests that an EAC wide monetary union is currently not possible based on the evidence provided from the pass-through analysis.
Keywords: East African Community -- Economic integration; East African Community -- Economic conditions -- 21st century; Interest rates -- Africa, East; Interest rates -- Econometric models -- Africa, East; Interest rates -- Effect of inflation on -- Africa, East; Banks and banking -- Africa, East